A prospective randomized study for comparison of haemodynamic changes and recovery characteristics with propofol and sevoflurane anaesthesia during laparoscopic cholecystectomies - Khare, Arvind; Mathur, Veena; Jain, Kavita; Sethi, Surendra K.; Garg, Deepak; Vishnoi, Raghunath (International Journal of Research in Medical Sciences, 2016)
Background: Day care laparoscopic surgical procedures are rapidly increasing nowadays. Rapid emergence and early recovery from anaesthesia with minimal complications are desired. Both propofol and sevoflurane meet above criteria and established as agents of choice in laparoscopic surgeries for induction and maintenance of anaesthesia. So this study aimed to compare sevoflurane with propofol for intraoperative haemodynamic changes with postoperative recovery profile in patient’s undergone laparoscopic cholecystectomies under general anaesthesia. Methods: In this prospective randomized study, sixty patients of either sex, 18-60 years with ASA grade 1 and 2 scheduled for laparoscopic cholecystectomies under general anaesthesia were randomly allocated into two groups. In Group S, patients were maintained on sevoflurane anaesthesia (0.5-2.5%) while in Group P, patients were maintained with propofol infusion (75-125 µg/kg/min) along with O2 (50%) and N2O (50%).The intraoperative haemodynamic parameters, recovery characteristics and postoperative nausea and vomiting (PONV) were observed in both groups. Results: The mean baseline haemodynamic parameters (HR, SBP, DBP, MBP, SpO2 and EtCO2) were comparable in both groups, (P>0.05). No significant difference in HR was at observed any time interval, P>0.05, however, SBP, DBP and MBP were significantly lower in propofol group at different time intervals, P<0.05, but clinically not significant and patients remained haemodynamically stable in both groups. The mean time for all recovery characteristics were significantly shorter in sevoflurane group as compared to propofol group, (P<0.01). However the incidence of PONV was significantly more in sevoflurane group. Conclusions: Sevoflurane can be used as an effective alternative to propofol for maintenance of anaesthesia in day care laparoscopic procedures as it has better recovery profile with stable haemodynamic parameters.